High Quality Monolayer Graphene Synthesized by Resistive Heating Cold Wall Chemical Vapor Deposition. (5th June 2015) - Bointon, Thomas H.; Barnes, Matthew D.; Russo, Saverio; Craciun, Monica F.
<x xml:space="preserve">Abstract</x> The growth of graphene using resistive‐heating cold‐wall chemical vapor deposition (CVD) is demonstrated. This technique is 100 times faster and 99% lower cost than standard CVD. A study of Raman spectroscopy, atomic force microscopy, scanning electron microscopy, and electrical magneto‐transport measurements shows that cold‐wall CVD graphene is of comparable quality to natural graphene. Finally, the first transparent flexible graphene capacitive touch‐sensor is demonstrated.